JavaScript Quick Syntax Reference - Olsson, Mikael. (Apress : Imprint: Apress, 2015)
JavaScript Quick Syntax Reference is a condensed syntax reference to the JavaScript language. It presents the essentials of JavaScript in a well-organized format that can be used as a handy reference. This includes the latest ECMAScript 5, JSON (JavaScript Object Notation) and DOM (Document Object Model) specifications and implementations. You won’t find any technical jargon, bloated samples, drawn out history lessons or witty stories in this book. What you will find is a JavaScript reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any JavaScript programmer or Web developer. In JavaScript Quick Syntax Reference, you will find a concise reference to JavaScript programming language syntax; has short, simple and focused code examples; and includes a well laid out table of contents and a comprehensive index allowing easy review.